Case Report: Are You One of Us and Can We Trust You?: Taking a Communication Perspective in Participatory Research - Fisher-Yoshida, Beth (Frontiers in Communication, 2021)
This article focuses on the necessity to build relationships with people across cultures, while doing participatory action research (PAR). There are many assumptions that are attached to the term “participation” and it is not only worth exploring how these assumptions are formed and how they might manifest during the course of the participatory action research project, but necessary to build trusting relationships. It is also important to manage how different voices are heard and which are privileged over others, as well as, how researchers with more formal experience and processes of research blend in partnership with those possessing local knowledge and practices. These many influences shape the dynamics of the relationships and efficacy of the work and this complexity needs to be considered and addressed. Setting priorities and becoming aware of the moral or “logical” forces that are attached to any of the contexts we prioritize is key in developing self-awareness. These contextual influences are culturally bound and in order to have equitable participatory processes across cultures, becoming more aware of the origin of these tendencies is critical. In addition, the more self-aware researchers become, as well as, the local partners, the more it will lead to developing better partnerships in these PAR processes.